The association between HLA-DQA1, HLA-DQB1 and HLA-DRB1 LOCI with graves disease in Thai Population - Thidathip Wongsurawat (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 2003